Brick sand particles as an adsorbent in column chromatography to remove heavy metals from solution - Hossain, Delwar; Prodhan, Md Minal Hossain; Hossain, Md Nazim; Dipti, Sharmin Sultana; Azad, Md Abul Kalam; Karim, Md Anwarul (Bangladesh Journal of Scientific and Industrial Research, 2024)
The column chromatography method was used with brick sand particles as an adsorbent for the removal of heavy metals (Cr, Fe, and Pb) from the aqueous solution. These metals can pollute water, and soil and also come in contact with the food chain, causing life-threatening health issues in the human body. The pore volume and the specific surface area of the brick sand particles were determined using the standard method which was 44.41% and 29.4 m2/g respectively. The different concentrations of toxic metals in the water solution were considered to determine the adsorption capacity of the adsorbent. The adsorption methods were able to remove about 94% of Cr, 24% Pb, and 69% Fe from the aqueous solution. From the investigation results, we may conclude that raw brick sand particles can play a vital role as an adsorbent in the treatment of heavy metal-contaminated wastewater. Moreover, the saturated adsorbent can be used as an element of construction materials to prevent further pollution. Bangladesh J. Sci. Ind. Res. 59(1), 47-54, 2024